Who is a Real Man? The Gender of Trumpism - CJ Pascoe (Masculinities and Social Change, 2017)
The rise of Trumpism exemplifies a contest over masculinity, over who qualifies as a “real man.” This contest being waged not only by some obvious actors – President Trump, his supporters and representatives; it is a contest also waged by those who oppose the current administration and are perhaps actively working against the perpetuation of gender inequality. The themes deployed by Trumpists and anti-Trumpists alike address a core component of masculinity in the global west – dominance. Through sexualized processes of confirmation and repudiation multiple actors in this political and social moment draw on and deploy understandings of normative masculinity as dominance – dominance over women and dominance over other, less masculine, men. Both the Trumpist and anti-Trumpist movements exemplify similar discourses of masculinized dominance in which social actors claim masculinity through discourses and symbols of “compulsive heterosexuality” and divest others of it through the emasculating practices of a “fag discourse.” The story of Trumpism and movements against it is an example of the tenacity of inequality in gendered discourses.